Constitutional Design: Separation of Financing and Project Decision - Hans Gersbach; Volker Hahn; Stephan Imhof (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
We examine the provision of public projects under separate tax and subsidy rules. We find that tax rules separated from project cum subsidy decisions exhibit several advantages when incentive problems of the agenda-setter are taken into account. In particular, tax rules may prevent the proposal of inefficient projects which benefit only a small lobby group. We propose “redistribution efficiency” as a socially desirable property of proposals and find that tax rules always guarantee redistribution efficiency. We show that rules on subsidies combined with discretion regarding taxes always yield socially inferior proposals. Finally, tax rules induce the agenda-setter to look for potential improvements of public projects.
Keywords: D72; H40; 330; constitutional design; provision of public projects; voting; taxes and subsidies; Öffentlicher Sektor; Projektfinanzierung; Politische Entscheidung; Steuerwirkung; Wahlverhalten; Wohlfahrtsökonomik